Effect of granular properties on hydrodynamics in coarse-grid riser flow simulation of Geldart A and B particles - Rashid, Taha Abbas Bin; Zhu, Li-Tao; Luo, Zheng-Hong (Powder technology, 2020)
In this work, a three-dimensional coarse-grid two-fluid model (TFM) simulation by varying granular properties like granular viscosity, frictional viscosity, and solids pressure has been performed. Simulated predictions were subsequently compared with experimental results in the case of Geldart A or B particles. Laminar flow behavior is also studied and coarse-grid simulation predictions were less realistic for laminar flow. This flow regime which although consumes less computational resources falls short for large-scale riser scale up. Flow regime in our simulation was fast fluidization and simulation predicts with minimum error near riser inlet. More specifically, granular viscosity, frictional viscosity and solids pressure for Type A particles predict with minimum error especially near riser inlet at a lower height. For Type B particles, these three solid properties correspond closely with experimental results near inlet at a lower height whereas, at a higher height, turbulence increases and simulation results deviate from experimental studies. [Display omitted] •A sub-grid drag model has been used.•Coarse-grid two-fluid simulation has been performed.•Laminar and turbulent flow behavior has been compared.•Granular property effect on flow behavior has been systematically assessed.